A study of the charring of datong coal under nitrogen and carbon dioxide atmospheres with particular reference to nano-particle formation - Irfan, M.F.; Daud, W.M.A.W. (2011)
Different chars are produced from Datong coal using thermo-gravimetric analyser having thermo-plus II software under different environments i.e. CO2 and N2 and different parametric conditions such as variations of temperature, flow rate etc. The produced chars are then subsequently analysed with field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (XPS) and Brunauer Emmett Teller (BET) surface area analyses in order to observe their structural properties. Thermo-gravimetric (TG) profiles of the produced chars are also presented and from these profiles it is observed that, at high temperatures and low flow rates, the weight loss percent of coal in CO2 is higher than under an N2 environment. This may be due to one additional step of coal gasification i.e. char gasification by CO2 at higher temperatures. FESEM images show the formation of perfect hexagonal nanorod structures of char produced under CO2 environment at a particular temperature of 773 K. Moreover, these images clearly show that, the amount and the dimension (size and shape) of nanorods are decreased and rods of smaller aspect ratio are observed with the increase of both flow rate and temperature as well. However, no such nanorods are observed when the char is produced under N2 environment. Moreover, measured BET surface areas are also very high in CO2 environment than N2 environment which may be due to the greater exposure of internal surface area created by the char-CO2 gasification reaction.